Kesenjangan Mutu di Sekolah Dasar: Studi Lapangan di SD Negeri 2 Kalisari, Banyuglugur – Situbondo - Juwita; Arini Noura Darina; Misbahul Arifin; Dian Zulfatul Iman; Faiq Julia Iqna’a (Education Reserach Center, 2025)
This research focuses its study on the gap in the quality of education in elementary schools located in mountainous areas with medium accreditation, by taking a field study at SDN 2 Kalisari. The main focus of this research is to identify factors that cause inequality in the quality of education, particularly those related to access to technology, student achievement and participation, and parental and community involvement. The method used is a qualitative approach with a case study type, where data is collected through observation, in-depth interviews, and documentation from the principal, teachers, and students. The results of the study show that limited digital facilities and internet networks, weak student literacy skills, and minimal support from the family and community environment are the main obstacles in realizing quality education. The implications of these findings emphasize the importance of contextual and equitable policy interventions, as well as the need for collaboration between schools, government, and communities to address the gap in education quality in remote areas.